Physiological Aspect of Menstruation - Jum Natosba (Arkus, 2015)
Menstruation or menarch or menstruation or menstruation is a normal physiological process for women, except during pregnancy. Menstruation is a sign of the fertile cycle and is a characteristic of female maturity which is marked by the process of removing blood from the uterus accompanied by periodic pieces of the lining of the uterine wall during the reproductive age Dismenorrhea is a medical condition characterized by severe uterine pain during menstruation that manifests as cyclical lower abdominal pain. This is the main cause of the decline in the quality of life of adolescents. This literature review aims to describe physiological process of menstruation.